2012
DOI: 10.1177/1933719111432870
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 are Differentially Expressed in Endometriosis

Abstract: Epigenetic mechanisms have been ascribed important roles in endometriosis. Covalent histone modifications at lysine residues have been shown to regulate gene expression and thus contribute to pathological states in many diseases. In endometriosis, histone deacetylase inhibition (HDACi) resulted in reactivation of E-cadherin, attenuation of invasion, decreased proliferation of endometriotic cells, and caused lesion regression in an animal model. This study was conducted to assess basal and hormoneregulated gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 47 publications
6
55
0
1
Order By: Relevance
“…19,20 However, HDAC-8 is expressed only in human tissues with smooth muscle differentiation. 21,22 The expression of HDAC-1 and -2 in endometriosis has also been investigated by Colón-Díaz et al 23 They found higher levels of HDAC-1 protein staining in endometriosis compared with control endometrium as well as slightly higher HDAC-2 levels in certain cases of endometriosis. However, significant differences were found in the localizations for HDAC-1 and -2 in the umbilicus and for HDAC-2 in the stroma of eutopic endometrium from patients with endometriosis compared with normal endometrium in the secretory phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, HDAC-8 is expressed only in human tissues with smooth muscle differentiation. 21,22 The expression of HDAC-1 and -2 in endometriosis has also been investigated by Colón-Díaz et al 23 They found higher levels of HDAC-1 protein staining in endometriosis compared with control endometrium as well as slightly higher HDAC-2 levels in certain cases of endometriosis. However, significant differences were found in the localizations for HDAC-1 and -2 in the umbilicus and for HDAC-2 in the stroma of eutopic endometrium from patients with endometriosis compared with normal endometrium in the secretory phase.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Colón-Díaz et al, several endometriotic samples from rare localizations were included in contrast to our study that used a classification in ovarian, peritoneal, and deepinfiltrating endometriosis. 23,24 Additionally, the tissue that was examined in the study by Colón-Díaz et al was collected from patients in different phases of the menstrual cycle, whereas all of the tissue samples in our study were collected from patients in the proliferative phase.…”
Section: Discussionmentioning
confidence: 99%
“…16 All the biopsies were evaluated by a pathologist to confirm the diagnosis of endometriosis. The total number of cores in the TMA were 34 peritoneal endometriosis, 29 ovarian endometriosis, 16 fallopian endometriosis, 7 gastrointestinal (GI) endometriosis, 4 skin endometriosis, 38 secretory phase endometrium, 14 control proliferative phase endometrium, and 22 eutopic endometrium of women with endometriosis.…”
Section: Immunohistochemistry Of H3k27me3 In Human Endometrial and Enmentioning
confidence: 99%
“…14,15 We have previously shown that endometriotic lesions are characterized by hypoacetylation of H3K9 and H3K16 and hypermethylation of H3K4, H3K9, and H3K27. 16,17 Based on these findings, we aimed to further study the relevance of H3K27me3 specifically in endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, strong evidence for a role of histone acetylation in endometriosis has been published, including the observation of a higher expression of HDACs in endometriotic tissues and the ablation of the endometriotic phenotype in vitro and in vivo by HDAC inhibition (HDACi), although the specific mechanisms involved are still under investigation. [8][9][10][11] These studies are of high translational relevance since HDACi has been proposed as a possible therapeutic strategy for endometriosis based on its effects on cell proliferation and apoptosis. 4 There is increasing evidence to suggest the existence of a ''histone code,'' the specific histone modification pattern that characterizes a particular differentiation or pathological state.…”
Section: Introductionmentioning
confidence: 99%